2011
DOI: 10.1002/hep.24221
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative hepatitis B surface antigen and hepatitis B e antigen titers in prediction of treatment response to entecavir

Abstract: Quantitative hepatitis B surface antigen (qHBsAg) and quantitative hepatitis B e antigen (qHBeAg) titers are emerging as useful tools for measuring viral loads and for predicting the virological response (VR) and serological response (SR) to pegylated interferon therapy. However, the clinical utility of these assays in patients taking entecavir (ETV) is largely unknown. Treatment-naive patients with chronic hepatitis B (CHB) who were taking ETV for 2 years were enrolled. The qHBsAg and qHBeAg levels were seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 29 publications
8
112
2
4
Order By: Relevance
“…Bir çok çalışmada HBsAg ve HBeAg değerleri benzer şekilde ölçülerek tedavinin izlenmesinde kullanılabilirlikleri değerlendirilmiştir (6,7,9,10,12,13,17,18). Ancak bu çalışmada hastalardan eş zamanlı alınan serum örneklerinde HBsAg, HBeAg ölçüm değerleri HBV DNA ve ALT düzeyleri ile karşılaştırılmış ve sonuçların araştırıcılar için yol gösterici olacağı düşünülmüştür.…”
Section: Discussionunclassified
“…Bir çok çalışmada HBsAg ve HBeAg değerleri benzer şekilde ölçülerek tedavinin izlenmesinde kullanılabilirlikleri değerlendirilmiştir (6,7,9,10,12,13,17,18). Ancak bu çalışmada hastalardan eş zamanlı alınan serum örneklerinde HBsAg, HBeAg ölçüm değerleri HBV DNA ve ALT düzeyleri ile karşılaştırılmış ve sonuçların araştırıcılar için yol gösterici olacağı düşünülmüştür.…”
Section: Discussionunclassified
“…The quantification of hepatitis B surface antigen (HBsAg) and hepatitis B virus (HBV) DNA levels is expected to play an important role in predicting and evaluating antiviral therapy responses in patients with chronic HBV hepatitis [1,2]. Recent studies suggested that the slow kinetics of covalently closed circular DNA (cccDNA) under powerful antiretroviral treatment is a main cause of viral rebound after interruption of longterm therapy [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In HBeAg-positive patients, those who have HBeAg loss tend to have a faster decline in HBsAg level, but the value of serum HBsAg to determine treatment cessation is uncertain [26,27]. In HBeAg-negative patients, small studies in Hong Kong and Taiwan suggested that serum HBsAg <100-200 IU/mL can predict sustained response and HBsAg seroclearance after stopping lamivudine, but these results need to be validated in bigger studies and other patient populations (Table 4) [28,29].…”
Section: Hbsag: From Qualitative To Quantitativementioning
confidence: 99%